Characteristics of Patient Safety Incident Occurrences Reported by Japanese Homecare Nurses: A Prospective Observational Study - Natsuki Yamamoto-Takiguchi; Takashi Naruse; Mahiro Fujisaki-; Noriko Yamamoto-Mitani (MDPI AG, 2021)
Patient safety incidents (PSIs) prevention is important in healthcare because PSIs affect patients negatively and increase medical costs and resource use. However, PSI knowledge in homecare is limited. To analyze patient safety issues and strategies, we aimed to identify the characteristics and contexts of PSI occurrences in homecare settings. A prospective observational study was conducted between July and November 2017 at 27 Japanese homecare nurse (HCN) agencies. HCNs at each agency voluntarily completed PSI reports indicating whether they contributed to PSIs or were informed of a PSI by the client/informal caregiver/other care provider during a period of three months. A total of 139 PSIs were analyzed, with the most common being falls (43.9%), followed by medication errors (25.2%). Among the PSIs reported to the HCN agencies, 44 were recorded on formal incident report forms, whereas 95 were reported as PSIs that required a response (e.g., injury care) but were not recorded on formal incident report forms. Most PSIs that occurred when no HCN was visiting were not recorded as incident reports (82.1%). Developing a framework/system that can accumulate, analyze, and share information on PSIs that occur in the absence of HCNs may provide insights into PSIs experienced by HCN clients.